Efektivitas Model Pembelajaran Observasi dalam Meningkatkan Hasil Belajar Mata Pelajaran IPS Kelas VIII di SMP Muhammadiyah 21 Serbelawan Tahun Ajaran 2023-2024 - Asnewastri, Asnewastri; Hutauruk, Ahmad Fakhri; Hiriani, Tera; Ginting, Andres M.; Hasugian, Jalatua H. (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2024)
This study aims to analyze the effectiveness of the observational learning model in improving the learning outcomes of eighth-grade students in Social Studies (IPS) at SMP Muhammadiyah 21 Serbelawan in the 2023-2024 academic year. The research method used is classroom action research (PTK) consisting of two cycles, each consisting of planning, implementation, observation, and reflection stages. Data were collected through learning outcome tests, observations, and interviews with students and teachers. The results showed that the implementation of the observational learning model can significantly improve student learning outcomes. In the first cycle, there was a 15% increase in the average student learning outcomes, and in the second cycle, the increase reached 25%. In addition, students showed higher enthusiasm and active involvement in the learning process. The conclusion of this study is that the observational learning model is effective in improving IPS learning outcomes and can be applied as an alternative learning method at SMP Muhammadiyah 21 Serbelawan.